The role of innate immune signals in immunity to Brucella abortus - Gomes, Marco Tulio R.; Campos, Priscila C.; de Almeida, Leonardo A.; Oliveira, Fernanda S.; Costa, Miriam M.; Marim, Fernanda M.; Pereira, Guilherme S.; Oliveira, Sergio C. (Frontiers in Cellular and Infection Microbiology, 2012)
Innate immunity serves as the first line of defense against infectious agents such as intracellular bacteria. The innate immune platform includes Toll-like receptors (TLRs), retinoid acid-inducible gene-I-like receptors and other cytosolic nucleic acid sensors, nucleotide-binding and oligomerization domain-like receptors, adaptors, kinases and other signaling molecules that are required to elicit effective responses against different pathogens. Our research group has been using the Gram-negative bacteria Brucella abortus as a model of pathogen. We have demonstrated that B. abortus triggers MAPK and NF-κB signaling pathways in macrophages in a MyD88 and IRAK-4-dependent manner. Furthermore, we claimed that so far TLR9 is the most important single TLR during Brucella infection. The identification of host receptors that recognize pathogen-derived nucleic acids has revealed an essential role for nucleic acid sensing in the triggering of immunity to intracellular pathogens. Besides TLRs, herein we describe recent advances in NOD1, NOD2, and type I IFN receptors in innate immune pathways during B. abortus infection.